Agricultural intensification and fertilizer use - Nin-Pratt, Alejandro (International Food Policy Research Institute, 2016)
A general question deriving from the preceding chapter is, what is the best approach for increasing agricultural productivity sustainably across and within different agricultural production zones? For example, is Asia’s Green Revolution model of high-yielding cereal varieties, fertilizer, and intensive use of labor a viable approach for Africa? A common answer to this question is there is little incentive to adopt labor-intensive technologies like those promoted by the Asian Green Revolution, because population densities in Africa are low compared with those in many of the Asian countries. This implies that farmers in Africa will not find profitable technologies that save land (abundant) and use labor (scarce and relatively more expensive) more intensively (Binswanger and Pingali 1988). This does not mean that Africa is at a disadvantage compared with Asia regarding adopting high-yielding varieties or using chemical inputs like fertilizer, herbicides, and pesticides more intensively. What it actually means is that the path that many countries in Africa will follow to incorporate new technology and increase production and productivity in agriculture will be different from the path followed by Asian countries.